From a brewer to the faraday of statistics: William Sealy Gosset - Abhay B Mane (Wolters Kluwer Medknow Publications, 2016)
William Sealy Gosset (1876-1937) was an immensely talented statistician to be remembered for his contributions to the development of modern statistics. Better known to the statistical world by his pseudonym, "Student," Gosset's name is associated with the discovery of the t-distribution and its use. He was a brewer of Guinness' Brewery in Dublin, Leinster, Ireland and the pioneer in the analysis of small samples. The most famous work, "The Probable Error of a Mean," published in "Biometrika" made a clear distinction between population parameters and sample estimates of them. He will be remembered as a practical scientist for his discoveries of the frequency distribution of the variance of normal samples and of the ratio of the mean to the standard deviation to the theory of statistics. His life was one full of fruitful scientific ideas that the Student's test of significance finds a unique place in the history of scientific method.